Dimensions of Philosophy of Science and the History of its Development - Fajar Solihin; Maspuroh; Maya Mardiana; Siti Fitria Firmansyah (Penerbit Hellow Pustaka, 2025)
Philosophy of science is a discipline that studies the foundations of scientific knowledge by considering various important dimensions.The cultural dimension examines how social values and norms influence the development and acceptance of science.The historical dimension examines the evolution of science over time,including changes in scientific paradigms.The humanitarian dimension evaluates the impact of science on people’s lives,including the benefits as well as the ethical dilemmas that arise.The reaction dimension addresses criticism of scientific community’s response to skepticims and epistemological issues.The system and structure of science refers to the methodological and logical framework that underlies the development of scientific theories, and how this framework can promote or hinder the advancement of knowledge.Through these dimensions,philosophy of science evaluates the validity and role of scientific knowledge in human.